2019
DOI: 10.3390/foods8070263
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Safety and Quality Parameters for Preparation of Jellyfish Based Novel Food Products

Abstract: Edible jellyfish are mainly consumed and marketed in Southeastern Countries, generally produced by a multi-phase drying process, using mixtures of salt and alum. Recently, jellyfish have become very attractive also for Western food markets. They are novel food in Europe and no recognized handling/processing steps have been set up yet. Moreover, no specific food safety and quality parameters are available. In this study, we identified a set of safety and quality parameters for jellyfish, based on standards and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 29 publications
0
48
0
Order By: Relevance
“…So far, a limited number of studies explored different types of interactions between marine microbial communities and scyphozoan jellyfish, from host-microbiome interactions to quali-quantitative changes of microbial composition sampled across different life stages, medusa body parts, water samples, mostly on common semeostome jellyfish [22,23,35,38,[49][50][51][52][53][54][55]. To our knowledge, Mastigias papua, Cotylorhiza tuberculata, and Rhizostoma pulmo are the only rhizostome jellyfish species previously investigated with respect to their associated microbial community [39,50,51,55,56].…”
Section: Introductionmentioning
confidence: 99%
“…So far, a limited number of studies explored different types of interactions between marine microbial communities and scyphozoan jellyfish, from host-microbiome interactions to quali-quantitative changes of microbial composition sampled across different life stages, medusa body parts, water samples, mostly on common semeostome jellyfish [22,23,35,38,[49][50][51][52][53][54][55]. To our knowledge, Mastigias papua, Cotylorhiza tuberculata, and Rhizostoma pulmo are the only rhizostome jellyfish species previously investigated with respect to their associated microbial community [39,50,51,55,56].…”
Section: Introductionmentioning
confidence: 99%
“…The latest studies have reported that some native jellyfish species present in the Mediterranean Sea have biochemical and textural features similar to edible Asiatic ones [17,36] and seem to be good candidates as a new "local seafood product". Jellyfish are extremely perishable raw materials and are generally treated within a few hours of collection to avoid deterioration, thus maintaining the organoleptic and safety qualities [37]. An essential prerequisite for the authorization of a novel food and its inclusion in the Union list by the EU Commission is that it must not cause any safety risks to human health on the basis of the available scientific data [27].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should consider metagenomics and metabolomics approaches for the analysis of raw and processed jellyfish. This could be interesting for obtaining information on total microbiota associated to jellyfish and qualitative and quantitative data on microbial metabolites to estimate other sources of microbiological risk for humans [37]. The allergenic risk could be related to the transformation degree of the product (raw or cooked) and to the length of jellyfish peptides acting as antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Microalgae, seaweed and jellyfish have been studied and screened for potential product development in terms of the reuse of their biomass as fertilizers or biostimulants, or feed and food (Bleve et al, 2019;Leone et al, 2019;Torres et al, 2019). Seaweeds have already been used in the food processing industry (e.g., for production of agar, alginates), but many other applications are possible.…”
Section: Reusementioning
confidence: 99%
“…As well as marine flora, marine animals that are invasive or create problems might be reused as a source for industrial processing. Jellyfish biomass has been recently recognized as a novel food source from the Mediterranean Sea (Bleve et al, 2019;Leone et al, 2019), particularly as it has been known as a delicacy in eastern Asia for hundreds of years. Even though the jellyfish body is composed of 95% water, the remaining biomass is rich in proteins and bioactive compounds.…”
Section: Reusementioning
confidence: 99%